Electronic spectra and ionization potentials of halogen oxides using the fock space coupled-cluster method - Vaval, N; Manohar, Prashant Uday; Pal, S (Collection of Czechoslovac Chemical Communications, 2005)
The ionization potentials and excitation energies of halogen monoxides and dihalogen oxides are studied using fully size-extensive Fock space version of multi-reference coupled-cluster theory. The low-lying excited states of ClO-, FO-, Cl2O and F2O are obtained along with the ionization spectra of Cl2O and F2O. The adiabatic electron affinity of ClO, FO and the vertical detachment energy of ClO- and FO- are also presented.